Do emerging land markets promote forestland appropriation? Evidence from Indonesia - Vijesh V. Krishna; Unai Pascual; Matin Qaim (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2014)
This paper empirically examines the emergence and functioning of land markets and their impacts on deforestation in Sumatra, Indonesia. While the evolution of land markets is expected to promote deforestation activities by rural households, we find no sizeable impact, due to two major reasons. First, land transactions occur in cultural and spatial isolation from forest encroachment. Second, the emergence of speculative land markets, which could accelerate deforestation, is evaded through institutional constraints, primarily weak property rights on land. However, while land markets do not promote deforestation, they also do not deter forestland appropriation, because of ambiguous legal frameworks.
urn:nbn:de:gbv:7-webdoc-3939-4
Keywords: O13; Q12; Q15; Q23; R14; 330; Forest conservation; Indonesia; Land resources; Plantation crops; Property rights; Open access; Bodenmarkt; Bodenspekulation; Entwaldung; Bodenpreis; Bodenrecht; Indonesien; Sumatra